TEACHING ENGLISH THROUGH OUTDOOR EXPERIENTIAL LEARNING IN ISLAMIC STATE UNIVERSITY IN AMBON - NURLAILA SOPAMENA (al-Iltizam: Jurnal Pendidikan Agama Islam, 2016)
This study is concerned with investigating ways of students in teaching and learning in English through outdoor experiential learning. Senior in Harmer (2006) points out that when the students come to class they bring with them their own personalities and their learning expectations. Their behavior will also be influenced by their current circumstances and by what happens in the lessons. There is always, as well, the possibility of interpersonal tensions between students and between students and their teacher. Based on that, teacher have to know about students characteristics to plan the good way in teaching and learning of English. Learning English is still difficult for most students in Ambon. In English learning, students seldom practice their speaking because they are afraid of making mistakes. Harmer (2006) said that, students are often reluctant to speak because they are shy and are not predisposed to expressing themselves in front of other people, especially when they are being asked to give personal information or opinions. Language is an effective instrument to build relationship and to cooperate each other. Therefore, the students should learn how to speak correctly and fluently because the function of speaking is conveying the ideas and thoughts. This is related with Jazadi (2009) in Jakarta Post newspaper said that the poor English proficiency of Indonesian students, both in high school and university, is mostly because the country's system of teaching English still focuses on studying about a language rather than studying how to use the language. Ideally, six years of studying English at high school should be enough to create fundamental communicative competence. Students should, at least, be able to speak basic English conversation.